Los conflictos de agencia en las asociaciones: apuntes sobre la deficiente regulación del Código Civil sobre los deberes y obligaciones de los administradores de personas jurídicas no lucrativas - Chahud Cosío, Daniel (2024)
Agency theory analyzes the relationship between the ‘principal’ and the ‘agent’, as well as the conflicts arising from their interaction and their various interests. However, agency conflicts are not only possible in non-profit legal entities such as associations, but could be more frequent due to their nature. In this sense, this paper examines the role of the management bodies of civil associations in relation to potential conflicts between members and managers, and the insufficient regulation surrounding them. Given that not all individuals who participate in business activities under an associative structure have a complete understanding of corporate governance, the author points out that it is crucial for our legislation to serve as a guide to facilitate their participation and, consequently, reduce the possibility of conflicts between the different groups involved.